Female Genital Mutilation/Cutting: Innovative Training Approach for Nurse-Midwives in High Prevalent Settings - Samuel Kimani; Tammary Esho; Violet Kimani; Samuel Muniu; Jane Kamau; Christine Kigondu; Joseph Karanja; Jaldesa Guyo (Hindawi Limited, 2018)
Background. Female genital mutilation/cutting (FGM/C) has no medical benefits and is associated with serious health complications. FGM/C including medicalization is illegal in Kenya. Capacity building for nurse-midwives to manage and prevent FGM/C is therefore critical. Objective. Determine the current FGM/C knowledge and effect of training among nurse-midwives using an electronic tool derived from a paper-based quiz on FGM/C among nurse-midwives. Methods. Nurse-midwives n=26 were assessed pre- and post-FGM/C training using a quiz comprising 12 questions. The quiz assessed the following factors: definition, classification, determining factors, epidemiology, medicalization, prevention, health consequences, and nurse-midwives' roles in FGM/C prevention themes. The scores for individuals and all the questions were computed and compared using SPSS V22. Results. The mean scores for the quiz were 64.8%, improving to 96.2% p<0.05 after training. Before the training, the following proportions of participants correctly answered questions demonstrating their knowledge of types of cutting (84.6%), link with health problems (96.2%), FGM/C-related complications (96.2%), communities that practice FGM/C (61.5%), medicalization (43.6%), reinfibulation (46.2%), dissociation from religion (46.2%), and the law as it relates to FGM/C (46.2%). The participants demonstrated knowledge of FGM/C-related complications with the proportion of nurse-midwives correctly answering questions relating to physical impact (69.2%), psychological impact (69.2%), sexual impact (57.7%), and social impact (38.5%). Additionally, participant awareness of NM roles in managing FGM/C included the following: knowledge of the nurse-midwife as counselor (69.2%), advocate (80.8%), leader (26.9%), role model (42.3%), and caregiver (34.6%). These scores improved significantly after training. Conclusion. Substantial FGM/C-related knowledge was demonstrated by nurse-midwives. They, however, showed challenges in preventing/rejecting medicalization of FGM/C, and there were knowledge gaps concerning sexual and social complications, as well as the specific roles of NM. This underscores the need to implement innovative FGM/C training interventions to empower health professionals to better respond to its management and prevention.